Analisis Kecelakaan Kerja Menggunakan Metode Hazard and Operability Study (HAZOP) Pada UKM Peuyeum Bandung 1 - Amanda Septriannisa Sutadi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The process of making peuyeum carried out by UKM Peuyeum Bandung 1 is still done manually, where it is done for a long time and in the same position and the equipment used by UKM Peuyeum Bandung 1 does not meet occupational health and safety standards. In carrying out this work there may be risks. The aim of this research is to minimize risks in making peuyeum by UKM Peyeum Bandung 1. The type of research carried out is quantitative research. The conclusion of the research on risk identification and work safety at UKM Peuyeum Bandung 1 is that the results of hazard identification using HAZOP analysis at UKM Peuyeum Bandung 1 show that there are 5 sources of danger, namely worker attitudes, foreign objects in the work area, stove, peeler and washing area. One of the processes at the source of worker attitude hazards is getting an